Studies on neotropical Phasmatodea VIII: Revision of the genus Decidia Stål, 1875 with the description of a new species from Colombia (Phasmatodea: Pseudophasmatidae: Pseudophasmatinae: Anisomorphini) - Conle, Oskar V.; Hennemann, Frank H.; Ramírez-Mora, Manuel A.; Quiróz, John A. (Zootaxa, 2009)
The genus Decidia Stål, 1875 is revised with an updated description of the genus, descriptions of all four known species, illustrations and keys are provided. The male of the type-species Decidia soranus (Westwood, 1859) is described and illustrated for the first time and a re-description of the females is given. Examination of the Colombian Peruphasma doylei (Caudell, 1906) has shown this to belong in Decidia (n. comb.); the male is re-described and the previously unknown female described and illustrated for the first time. Also Autolyca blapoides Redtenbacher, 1906 from South Ecuador has proven to belong in Decidia and is here transferred (n. comb.) with the female re-described and unknown male described and illustrated for the first time. These two species show the genus Decidia to contain not only winged but apterous species as well. A very colourful new species, Decidia magnifica n. sp. from the central Cordillera of Colombia, is described and illustrated from both sexes. The eggs of Decidia remain as yet unknown. Decidia appears to be restricted to the Andean regions of Central and Southern Colombia and Ecuador above an altitude of 2000 metres, referred to as the biogeographical province Cauca. The genus shows close relation to the Central American Autolyca Stål, 1875 and is hence re-transferred from Pseudophasmatini to the tribe Anisomorphini (rev. stat.).